Pengaruh Citra Merek dan Persepsi Followers Instagram @Esqacosmetics Terhadap Keputusan Pembelian Produk Kosmetik ESQA - Rahmadhani, Ilham Suci; Dwi Adnjani, Made (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to determine the effect of the independent variable Brand Image and Perception of Instagram Followers @esqacosmetics on the dependent Purchase Decision of Esqa Cosmetic Products. The research approach used is eskplanatif with purposive sampling technique. The population in this study was 16-30 years old and the sample used was 220 respondents. This research data is quantitative by collecting data through questionnaires. The data analysis technique used is multiple linear regression. The results in this study indicate that brand image has a significant effect while followers' perceptions have no significant effect on purchasing decisions.